Pengaruh lingkungan toko dan faktor situasional terhadap perilaku pembelian tak berencana - Muhammad Rizky Yasmuna; Pamasang S. Siburian; Asnawati Asnawati (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
this research on the influence of neighborhood shops and Situational Factors to purchase implusife buying, the purpose of this research to test, identify and explain the effect of store environment and Situational Factors to Purchase Impulsive. This research is classified in research explanations (explanatory research) and the method used is survey method. Anlisis tool data used is multiple linear regression analysis. Results of the study revealed that: From the results of validity and reliability in mind that the neighborhood store and Situational Factors to implusif buying. Everything is valid and reliable As of multiple linear regression analysis known that Toko Environmental and Situational Factors that have a significant influence on Impulse Buying at Giant Mart SCP. From the hypothesis testing known that unity hypothesis is accepted, it means there is simultaneously a significant influence between the variables of the Impulse Buying Environment Shops at Giant Mart. The second hypothesis is accepted, it means Situational factors are variables that affect the Impulse Buying at Giant Mart.